2014
DOI: 10.1152/jn.00720.2013
|View full text |Cite
|
Sign up to set email alerts
|

Axon diameters and conduction velocities in the macaque pyramidal tract

Abstract: Small axons far outnumber larger fibers in the corticospinal tract, but the function of these small axons remains poorly understood. This is because they are difficult to identify, and therefore their physiology remains obscure. To assess the extent of the mismatch between anatomic and physiological measures, we compared conduction time and velocity in a large number of macaque corticospinal neurons with the distribution of axon diameters at the level of the medullary pyramid, using both light and electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
116
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(134 citation statements)
references
References 81 publications
14
116
2
Order By: Relevance
“…Many panthers hunt by stalking and pouncing on prey, which demands a substantial burst of energy, considerable strength, and the quick recruitment/coordination of many muscle groups. In modulating downstream neuromuscular output, gigantopyramidal neurons in the motor cortex exhibit several functional characteristics that may make them particularly important for feliforms: (1) they appear to be able to synchronize their activity because of dendritic bundling (Meyer, ; Scheibel et al, ) and clustering (Groos, Ewing, Carter, & Coulter, ), particularly in the hand‐forepaw region (Rivara et al ); (2) they exhibit increased conduction velocities because of their large axonal diameter (Evarts, ; Firmin et al, ; Sakai & Woody, ), and are associated, at least indirectly, with increased striated muscle contraction velocity and power (Buller, Eccles, & Eccles, ; Kohn & Noakes, ; Salmons & Vrbová, ); and finally, (3) they appear to initiate incipient, patterned downstream motor activity quickly (Lundberg & Voorhoeve, ; Takahashi, ). These functional characteristics of gigantopyramidal neurons seem consistent with, if not a prerequisite for, the unusually short reaction times in feliforms (Kohn et al ; Kohn & Noakes, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many panthers hunt by stalking and pouncing on prey, which demands a substantial burst of energy, considerable strength, and the quick recruitment/coordination of many muscle groups. In modulating downstream neuromuscular output, gigantopyramidal neurons in the motor cortex exhibit several functional characteristics that may make them particularly important for feliforms: (1) they appear to be able to synchronize their activity because of dendritic bundling (Meyer, ; Scheibel et al, ) and clustering (Groos, Ewing, Carter, & Coulter, ), particularly in the hand‐forepaw region (Rivara et al ); (2) they exhibit increased conduction velocities because of their large axonal diameter (Evarts, ; Firmin et al, ; Sakai & Woody, ), and are associated, at least indirectly, with increased striated muscle contraction velocity and power (Buller, Eccles, & Eccles, ; Kohn & Noakes, ; Salmons & Vrbová, ); and finally, (3) they appear to initiate incipient, patterned downstream motor activity quickly (Lundberg & Voorhoeve, ; Takahashi, ). These functional characteristics of gigantopyramidal neurons seem consistent with, if not a prerequisite for, the unusually short reaction times in feliforms (Kohn et al ; Kohn & Noakes, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Vigneswaran et al () also reported spike durations of “unidentified” neurons in M1 (those not responding antidromically to PT stimulation). Because of size bias in cortical recordings (see Firmin et al, ), these spikes are unlikely to have come from interneurons. Instead, these “unidentified neurons” were more likely to be other large M1 pyramidal cells projecting to different subcortical structures (corticostriatal, corticorubral, corticobulbar, and so forth), but not to the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of axons in the CNS have fiber diameters below 4 µm [Liewald et al, 2014; Aboitiz et al, 1992], except pyramidal axons whose diameters, although predominantly between 2 µm and 4 µm, can range up to 12 µm [Firmin et al, 2014]. Nonetheless, it is the largest diameter axons that dominate the response to electrical stimulation due to their low stimulation thresholds [McNeal, 1976].…”
Section: Methodsmentioning
confidence: 99%